(E)-N′-(3,4-Dimethoxybenzylidene)-2,4-dihydroxybenzohydrazide methanol solvate - Qiao-Ling Zhang; Li-Zi Yin; Xu-Ming Deng; Song-Cai Liu; De-Guang Song (Acta Crystallographica Section E, 2009)
The title compound, C16H16N2O5·CH3OH, was obtained from a condensation reaction of 3,4-dimethoxybenzaldehyde and 2,4-dihydroxybenzohydrazide. The non-H atoms of the Schiff base molecule are approximately coplanar (r.m.s. deviation = 0.043 Å) and the dihedral angle between the two benzene rings is 1.6 (1)°. The molecule adopts an E configuration with respect to the C=N double bond. An intramolecular O—H...O hydrogen bond is observed. The Schiff base and methanol molecules are linked into a two-dimensional network parallel to (10overline{1}) by intermolecular N—H...O, O—H...N and O—H...O hydrogen bonds.